An impulse control approach for optimal maintenance scheduling of a gas turbine. Issue 1 (25th October 2016) - Gröger, Michael
Abstract: Today gas turbine outages are determined by one global life counter and deterministic life times. In the future the gas turbine will be equipped with multiple life counters for outage determination. Therefore we present an impulse control approach which takes the probabilistic nature of the damage mechanism into account to calculate an optimized maintenance schedule. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)